RGD-decorated PLGA nanoparticles improved effectiveness and safety of cisplatin for lung cancer therapy - Yadav B.; Chauhan M.; Shekhar S.; Kumar A.; Mehata A.K.; Nayak A.K.; Dutt R.; Garg V.; Kailashiya V.; Muthu M.S.; Sonali; Singh R.P. (My University, 2025)
Upon extensive pharmaceutical and biomedical research to treat lung cancer indicates that lung cancer remains one of the deadliest diseases and the leading cause of death in men and women worldwide. Lung cancer remains untreated and has a high mortality rate due to the limited potential for effective treatment with existing therapies. This highlights the urgent need to develop an effective, precise and sustainable solutions to treat lung cancer. In this study, we developed RGD receptor-targeted PLGA nanoparticles for the controlled and targeted co-delivery of cisplatin (CDDP) and upconversion nanoparticles (UCNP) in lung cancer therapy. Pluronic F127-RGD conjugate was synthesized by carbodiimide chemistry method and the conjugation was confirmed by FTIR and 1HNMR spectroscopy techniques. PLGA nanoparticles were developed by the double emulsification method, then the surface of the prepared nanoparticles was decorated with Pluronic F127-RGD conjugate. The prepared formulations were characterized for their particle size, polydispersity index, zeta potential, surface morphology, drug encapsulation efficiency, and in vitro drug release and haemolysis studies. Pharmacokinetic studies and safety parameters in BAL fluid were assessed in rats. Histopathology of rat lung tissue was performed. The obtained results of particle sizes of the nanoparticle formulations were found 100–200 nm, indicating the homogeneity of dispersed colloidal nanoparticles formulations. Transmission Electron Microscopy (TEM) revealed the spherical shape of the prepared nanoparticles. The drug encapsulation efficiency of PLGA nanoparticles was found to range from 60% to 80% with different nanoparticles counterparts. RGD receptor-targeted PLGA nanoparticles showed controlled drug release for up to 72 h. Further, RGD receptor-targeted PLGA nanoparticles achieved higher cytotoxicity in compared to CFT, CFT, and Ciszest-50 (marketed CDDP injection). The pharmacokinetic study revealed that RGD receptor-targeted PLGA nanoparticles were 4.6-fold more effective than Ciszest-50. Furthermore, RGD receptor-targeted PLGA nanoparticles exhibited negligible damage to lung tissue, low systemic toxicity, and high biocompatible and safety in lung tissue. The results of RGD receptor-targeted PLGA nanoparticles indicated that it is a promising anticancer system that could further exploited as a potent therapeutic approach for lung cancer. © 2023 Elsevier B.V.